2019
DOI: 10.32412/pjohns.v34i2.1097
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Tracheostomy, Weaning from Mechanical Ventilation and Duration of Hospitalization among a Sample of Pediatric Patients

Abstract: Objective: To determine if there is a difference in the duration of mechanical ventilation and hospitalization between patients who underwent early compared to late tracheostomy. Methods:      Design:                Causal-Comparative (ex post facto) Chart Review      Setting:                Tertiary National University Hospital      Participants:                   Records of 68 pediatric patients who underwent elective tracheostomy from January 1, 2013 to June 30, 2018 were considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The search did not return any randomized trials. The authors found eight studies 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 that compared the prognoses of patients undergoing “early” or “late” tracheostomy: in five, “early tracheostomy” was defined as being performed before 14 days of mechanical ventilation, and “late,” after this period. In two studies, “early” was defined as before seven days post-trauma injury, and, in one, as before ten days of ventilation ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The search did not return any randomized trials. The authors found eight studies 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 that compared the prognoses of patients undergoing “early” or “late” tracheostomy: in five, “early tracheostomy” was defined as being performed before 14 days of mechanical ventilation, and “late,” after this period. In two studies, “early” was defined as before seven days post-trauma injury, and, in one, as before ten days of ventilation ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“… <10 days of MV 37/33 Death in PICU 9.8 (7) 26.8 (12.9) 7 Lee et al, 2016 67 Retrospective cohort General PICU Age range: 1 mo. - 18 y ≤14 days of MV 61/50 30 days and 1 year-mortality 9.2 (5.4) 37.9 (30.6) 8 Ferrolino et al, 2019 68 Retrospective cohort General PICU Age range: 2 mo. - 12 y.…”
Section: Resultsmentioning
confidence: 99%